Analisis Peran Orang Tua Dalam Kecenderungan Perilaku Bullying - Diah Agustin; Muhammad Arsyad; Ali Rachman (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF THE ROLE OF PARENTS IN THE TENDENCY OF BULLYING BEHAVIOR This study aims to analyze the role of parents in adolescents' tendency toward bullying behavior by examining parental affection, attention, parenting style, family dynamics, and emotional availability. A qualitative phenomenological approach was employed. Data were collected through in-depth interviews, observations, and documentation involving school counselors, parents, students, and school records. The data were analyzed using thematic analysis supported by NVivo 12 Pro, while data credibility was ensured through source and technique triangulation. The findings indicate that although parents adequately fulfill their children's physical and educational needs, emotional needs remain insufficiently addressed. Family communication tends to be one-way, emotional relationships lack warmth, parenting practices emphasize control through reprimands and punishment rather than dialogue, and parental supervision has not fully captured the children's social experiences. As a result, children receive limited emotional support, have fewer opportunities to express their problems, and lack positive models for constructive conflict resolution. The study concludes that low emotional warmth, limited open communication, authoritarian parenting tendencies, and inadequate parental supervision contribute to adolescents' tendency to engage in bullying behavior. Therefore, bullying prevention should focus on strengthening parenting quality, fostering open family communication, and increasing parents' emotional involvement in their children's development.